PEMILIHAN SUPPLIER LAMPU UV DALAM PEMBUATAN BOX STERILIZATION MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Wira Daniel Pratama; Yetriuli R Sianturi; Alvin P Silaen; Indra H Sitorus; Benedikta A.H. Siboro (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2021)
Box Sterilization is an innovative product designed as a tool to sterilize equipment and objects to prevent the risk of transmitting Covid-19 through contaminated objects. The Box Sterilization product has components that must be supplied from the supplier. One of the components needed from the supplier is a UV lamp. Currently there are two suppliers of UV lamp suppliers, there are AHCD Medan and Toko Utako. The company must take a decision to determine which suppliers are included in the alternative selection criteria. The company determines three variables which are the atribute of the criteria, there are price, quality and service, while for the sub-criteria atribute there are 6 variables, there are price compatibility, shipping costs, conformity of supply to specifications, ability to provide consistent quality, delivery service and supply warranty. The decision making for the supplier selection is done by using the Analytical Hierarchy Process (AHP) approach. The purpose of this study using the AHP method is for the company to be able to determine the priority of the attribute criteria, sub-criteria and alternatives to the selection of UV lamp suppliers for Box Sterilization. Based on data processing using AHP, it is found that the main priority for the criteria atributt is Quality, while the main priority for the sub-criteria atributt is the ability to provide consistent quality. Based on AHP analysis, it can be concluded that the most appropriate supplier of UV lamp suppliers for Box Sterilization is Medan AHCD supplier.